Developments in Amphibian Parental Care Research: History, Present Advances, and Future Perspectives - Schulte, Lisa M. (Herpetological Monographs, 2020)
Despite rising interest among scientists for over two centuries, parental care behavior has not been as thoroughly studied in amphibians as it has in other taxa. The first reports of amphibian parental care date from the early 18th century, when Maria Sibylla Merian went on a field expedition in Suriname and reported frog metamorphs emerging from their mother’s dorsal skin. Reports of this and other parental behaviors in amphibians remained descriptive for decades, often as side notes during expeditions with another purpose. However, since the 1980s, experimental approaches have proliferated, providing detailed knowledge about the adaptive value of observed behaviors. Today, we recognize more than 30 types of parental care in amphibians, but most studies focus on just a few families and have favored anurans over urodeles and caecilians. Here, we provide a synthesis of the last three centuries of parental care research in the three orders comprising the amphibians. We draw attention to the progress from the very first descriptions to the most recent experimental studies, and highlight the importance of natural history observations as a source of new hypotheses and necessary context to interpret experimental findings. We encourage amphibian parental care researchers to diversify their study systems to allow for a more comprehensive perspective of the behaviors that amphibians exhibit. Finally, we uncover knowledge gaps and suggest new avenues of research using a variety of disciplines and approaches that will allow us to better understand the function and evolution of parental care behaviors in this diverse group of animals.